2015
DOI: 10.3390/en8043118
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazine Borane and Hydrazinidoboranes as Chemical Hydrogen Storage Materials

Abstract: Abstract:Hydrazine borane N2H4BH3 and alkali derivatives (i.e., lithium, sodium and potassium hydrazinidoboranes MN2H3BH3 with M = Li, Na and K) have been considered as potential chemical hydrogen storage materials. They belong to the family of boron-and nitrogen-based materials and the present article aims at providing a timely review while focusing on fundamentals so that their effective potential in the field could be appreciated. It stands out that, on the one hand, hydrazine borane, in aqueous solution, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 65 publications
(129 reference statements)
2
51
0
Order By: Relevance
“…Borohydrides M(BH 4 ) n (with M as an alkali, alkaline-earth or metal element and n = 1, 2, 3 or 4) and borane complexes L-BH 3 (with L as NH 3 or N 2 H 4 ) are typical candidates [2][3][4]. For example, the compounds lithium borohydride LiBH 4 , ammonia borane NH 3 BH 3 (AB) and hydrazine borane N 2 H 4 BH 3 (HB) carry 18.4, 19.5 and 15.4 wt. % H respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Borohydrides M(BH 4 ) n (with M as an alkali, alkaline-earth or metal element and n = 1, 2, 3 or 4) and borane complexes L-BH 3 (with L as NH 3 or N 2 H 4 ) are typical candidates [2][3][4]. For example, the compounds lithium borohydride LiBH 4 , ammonia borane NH 3 BH 3 (AB) and hydrazine borane N 2 H 4 BH 3 (HB) carry 18.4, 19.5 and 15.4 wt. % H respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These theoretical hydrogen densities are among the highest. Another example is ammonium borohydride [NH 4 ][BH 4 ] with 24.6 wt. % H, but it is unstable dehydrogenating to AB at sub-zero temperatures [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 it was first found to be suitable as solid-state monopropellant for rocketry and fast hydrogen generating systems. 9 More recently, it was suggested to be a possible candidate for chemical hydrogen storage, 10 provided it is not used in pristine state. 7 Indeed, better dehydrogenation performance, in terms of onset temperature of reaction and release of unwanted gaseous side-products, can be obtained by adding a destabilizing agent (e.g., LiH, LiBH 4 , NH 3 BH 3 ), 11−13 or by chemically modifying the borane to form hydrazinidoborane derivatives (e.g., LiN 2 H 3 BH 3 , NaN 2 H 3 BH 3 , KN 2 H 3 BH 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our goal in assembling this special issue of Energies was to provide readers with a sense of the future directions that can be anticipated in metal hydride research in view of these changes. We hoped to accomplish this by providing a sampling of the variety of cutting-edge research efforts on metal hydrides that are currently underway throughout the scientific world.We are now happy to present the 15 outstanding contributions (13 original research papers and two reviews) that can be found within this special issue [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. With the inclusion of authors from 16 different countries, the issue truly presents a global view.…”
mentioning
confidence: 99%